The Year of Creativity and Innovation - Abd Razak, Dzulkifli (2010)
THE year 2010 has been designated as the Year of Creativity and Innovation, to be launched by the Prime Minister Datuk Seri Najib Razak in the coming weeks. Indeed, creativity and innovation are often said to be the next phase of development towards a developed country status. Only with these traits can we create new competitive advantages for individuals, societies and nations. Human beings are born imaginative and innovative but unfortunately we have been conditioned by our environment to be otherwise.